1986
DOI: 10.1177/074193258600700208
|View full text |Cite
|
Sign up to set email alerts
|

Child Abuse and Children With Handicaps

Abstract: A review of the factors contributing to parental physical abuse of children with handicaps is presented following a brief overview of the general pyitbtem of child abuse in the United States. Parental child abuse was found to be a response to an interaction of variables within the parent, child, and envimnment. These variables were found to be associated with many characteristics of families who had children with handicaps. Also, characteristics of abused children were faund to be similar to characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Despite using a small sample of only seven mothers and their twin infants, Mann (1992) demonstrated that, at 8 months, the healthier twin, rather than the twin who was more fun or who first left the hospital, received more positive maternal responses. Moreover, infants with physical disabilities or chronic diseases are at high risk of maltreatment and infanticide (Daly and Wilson 1988;Sullivan andKnutson 1998, 2000;Zirpoli 1986;Zirpoli and Bell 1987). That is especially true when parents are young and have more opportunities to birth future babies (Tifferet et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Despite using a small sample of only seven mothers and their twin infants, Mann (1992) demonstrated that, at 8 months, the healthier twin, rather than the twin who was more fun or who first left the hospital, received more positive maternal responses. Moreover, infants with physical disabilities or chronic diseases are at high risk of maltreatment and infanticide (Daly and Wilson 1988;Sullivan andKnutson 1998, 2000;Zirpoli 1986;Zirpoli and Bell 1987). That is especially true when parents are young and have more opportunities to birth future babies (Tifferet et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, little research has focused on the provision of services for families with children who are developmentally delayed or handicapped (White et al, 1987;Zirpoli, 1986). Research efforts may be limited because prevention and treatment services that reflect a child-focused view of risk are not practical at a clinical level.…”
Section: Clinical Level: Assessment and Treatmentmentioning
confidence: 96%
“…Frodi (1981) and Morgan (1987) described the prolonged, aversive cry of premature infants as an elicitor of abuse and neglect. Zirpoli (1986) and Leventhal et al (1987) reported that children with handicaps who were unresponsive or exhibited poor temperament were at risk for abuse and neglect. Frequently, however, the marker itself is implicated as the causal variable.…”
Section: Conceptual Levelmentioning
confidence: 97%
See 1 more Smart Citation
“…The majority of the literature on abuse of people with disabilities has focused on children (Diamond & Jaudes, 1983;Frisch & Rhoads, 1982;Green, Voeller, Gaines & Kubie, 1981;Money, 1982;Murphy, 1982;Nesbit, & Karagiania, 1982;Rose & Hardman, 198 1 ;Soeffing, 1975;Sandgrund, Gaines, & Green, 1974;Solomons, 1979;Starr, Dietrich, Fischhoff, Ceresnie, & Zwier, 1984;Valentine, 1990;Zirpoli, 1986;Zirpoli, 1990). These studies indicated that mental retardation may be a cause and an effect of child abuse.…”
mentioning
confidence: 91%